PENGARUH VARIASI TIMING INJECTION DAN CAMPURAN BAHAN BAKAR TERHADAP UNJUK KERJA MOTOR DIESE - Susanto, Taufiq Heri; Margianto, Margianto; Marlina, Ena (Jurnal Teknik Mesin, 2016)
Diesel engine is a type of internal combustion engine, fuel burn due to high compression pressure inside the cylinder. Comparison with the fuel-air mixture, timing fuel injection, and the amount of oxygen contained in dry air around, the operational aspects that affect the diesel engine. The purpose of this research was to study the characteristics of the diesel engine (torque, power, specific fuel consumption, and smoke opacity) on timing injection angle 14 , 18 , and 22 BTDC. The study was conducted with an experimental test on diesel engine fuel with biodiesel and coconut oil mixture with a percentage of a mixture of 0%, 5%, and 10% on a stationary diesel engine 2000 rpm. The result showed that the maximum torque of 140.98 Nm, 29.51 kW power and specific fuel consumption 0.468 kg / kWh at an angle of 14 BTDC with a mixture of coconut oil by 0%. While low smoke opacity 7.5% in coconut oil mixture in the fuel as much as 10% at an angle of 14 BTDC. Rewind the injection timing angle create torque, effective power and specific fuel consumption is less than optimal, while the use of coconut oil in the fuel can reduce smoke opacity levels in diesel engine.